DEVELOPMENT AND IMPLEMENTATION OF PEDAGOGICAL PROJECTS USING CREATIVE TECHNOLOGIES - Larysa Savchenko; Karyna Safian (Alfred Nobel University Journal of Pedagogy and Psychology)
The article explores the issue of designing and implementing pedagogical projects using creative technologies. It examines the potential of such technologies to support effective project-based learning in online formats, facilitating interactivity, feedback, and collaboration among participants in the educational process regardless of their physical location. The purpose of the article is to investigate the potential for applying creative technologies in the development and implementation of pedagogical projects, particularly in online formats, ensuring interactivity, feedback, and collaboration among all participants in the educational environment, regardless of their geographical location. The research employed general scientific methods such as analysis, monitoring, systematisation, and generalisation. In particular, monitoring was conducted to assess students’ readiness to apply pedagogical projects in their professional activities. A total of 111 students from Kryvyi Rih State Pedagogical University and the National University of Life and Environmental Sciences of Ukraine participated in the study. The relevance of the topic is reinforced by the challenges posed by distance and blended learning, which have become especially prominent in recent years. Pedagogical projects integrating creative technologies foster students’ original thinking and help develop key skills such as idea generation and unconventional problem-solving skills essential for personal and professional self-fulfilment in the modern world. The article outlines the objectives, tasks, and stages of pedagogical project implementation, providing examples of how creative technologies can be integrated into each stage. The nature of creative technologies has been clarified as a set of tools, methods, and approaches designed to stimulate, nurture, and implement innovative ideas and solutions. It has been highlighted that the use of creative technologies and AI-powered tools (e.g. mind maps, interactive posters/infographics, virtual and augmented reality, visual success stories, gamification) at each project stage not only enhances the development of students’ creative abilities but also makes the educational process more engaging and effective. A model for using pedagogical projects in the teaching of the compulsory course “Educational and Creative Technologies in Professional Practice” and the elective course “Innovative Technologies” has been presented. The content of several pedagogical projects – such as Individual Educational Trajectory, Coaching in Education, and Process Coaching: A Development Programme for Studying Key Concepts of Image – has been examined, alongside creative tasks and an overview of the applied technologies. The results of the project-based implementation indicate a significant increase in students’ cognitive and professional engagement and their willingness to apply knowledge and skills creatively in practice. It has been established that the application of creative technologies as a set of methods, tools, and strategies has had a positive impact on the development of crucial professional skills, particularly in the field of pedagogical project design. Students demonstrated their readiness to apply acquired knowledge creatively, indicating an increased level of professional maturity. This proves the positive impact of creative technologies on both learning and educational project development. It has been concluded that the integration of creative technologies into pedagogical project design is an effective tool for fostering students’ practical skills and creative potential, as well as for cultivating their creative abilities.